Synthesis of Poly[APMA]-DOTA-Cu Conjugates for Interventional Radionuclide Therapy of Prostate Cancer: Assessment of Intratumoral Retention by Micro–Positron Emission Tomography - Jianchao Yuan; Yezi You; Xin Lu; Otto Muzik; David Oupicky; Fangyu Peng (Molecular Imaging)
To develop new radiopharmaceuticals for interventional radionuclide therapy of locally recurrent prostate cancer, poly[ N -(3-aminopropyl)methacrylamide] [poly(APMA)] polymers were synthesized by free radical precipitation polymerization in acetonedimethylsulfoxide using N,N ‘-azobis(isobutyronitrile) as the initiator. The polymers were characterized with nuclear magnetic resonance, size exclusion chromatography, and dynamic light scattering ( M n 5 2.40 × 10 4 , M w / M n = 1.87). Subsequently, poly[APMA] was coupled with 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) using 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride as an activator, followed by conjugation with 64 Cu radionuclide. Prolonged retention of poly[APMA]-DOTA- 64 Cu conjugates within the tumor tissues was demonstrated by micro–positron emission tomography at 24 hours following intra-tumoral injection of the conjugates to human prostate xenografts in mice. The data suggest that the poly[APMA]-DOTA- 64 Cu conjugates might be useful for interventional radionuclide therapy of locally recurrent prostate cancer in humans.